1999
DOI: 10.1161/01.cir.99.8.990
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Angiotensin II Receptor Blockade to Maximal Angiotensin-Converting Enzyme Inhibition Improves Exercise Capacity in Patients With Severe Congestive Heart Failure

Abstract: Losartan enhances peak exercise capacity and alleviates symptoms in patients with CHF who are severely symptomatic despite treatment with maximally recommended or tolerated doses of ACE inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
110
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(112 citation statements)
references
References 12 publications
1
110
1
Order By: Relevance
“…In patients with stable CHF, small studies have shown that combined RAS blockade provided greater benefit than singlesite blockade on surrogate end points such as improvement in cardiac load and function, 44 increase in exercise capacity, 45 prevention of LV remodeling, and reduction of neurohormonal activation. 35 All these clinical studies share the same limitations: short treatment periods, small group sizes, administration of a nonstandardized ACE inhibitor treatment that was not at a predetermined maximal dose, and the use of a single fixed dose of an AT1R antagonist.…”
Section: Hf and Post-mi: Clinical Resultsmentioning
confidence: 99%
“…In patients with stable CHF, small studies have shown that combined RAS blockade provided greater benefit than singlesite blockade on surrogate end points such as improvement in cardiac load and function, 44 increase in exercise capacity, 45 prevention of LV remodeling, and reduction of neurohormonal activation. 35 All these clinical studies share the same limitations: short treatment periods, small group sizes, administration of a nonstandardized ACE inhibitor treatment that was not at a predetermined maximal dose, and the use of a single fixed dose of an AT1R antagonist.…”
Section: Hf and Post-mi: Clinical Resultsmentioning
confidence: 99%
“…Finally, the ancillary properties of both ACE inhibitors, eg, interruption of kinin metabolism and interaction with nitric oxide (NO), and of AT 1 receptor antagonists, eg, interaction with NO and prostaglandins may be active when the two agents are used singly, but may be synergistic when the groups are combined. 28 Additive effects on blood pressure and renin release in sodium-depleted normotensive adults 29 and on exercise capacity in heart failure patients 30 has been described recently when an ACE inhibitor is combined with an ATII AT 1 receptor antagonist. It may be argued that 12 of the patients were already on calcium channel blockers, which also have favourable effects on arterial wave reflection.…”
Section: Additive Effects Of Ace Inhibition and Angiotensin II Receptmentioning
confidence: 99%
“…17 The addition of AT 1 blockade to recommended or maximally tolerated ACEI was recently shown to improve exercise capacity and reduce symptoms in patients with heart failure. 18 Jorde et al 19 recently found, however, that maximally recommended doses of ACEI may be inadequate and that very-high-dose ACEI provided experimental hemodynamic effects similar to those with combined AT 1 blockade and standard-dose ACEI in patients with heart failure. The effects of combined ACEI and AT 1 antagonism on postinfarction LV remodeling are uncertain.…”
mentioning
confidence: 99%